Citrus Blackfly Parasitoid, Amitus hesperidum Silvestri (Insecta: Hymenoptera: Platygasteridae) - Ru Nguyen (EDIS, 2004)
Amitus hesperidum Silvestri is one of the most effective parasites of the citrus blackfly, Aleurocanthus woglumi Ashby. This parasite was described by Silvestri in 1927 from Aleurocanthus citriperdus in Hong Kong and Singapore (Silvestri 1927). It was collected in India and introduced into Mexico for controlling citrus blackfly (Smith et al. 1964). Because of the success in Mexico, it was imported into Texas (Summy et al. 1983) and Florida (Hart et al. 1978) to suppress the population of citrus blackfly in these states. This document is EENY-243 (originally published as DPI Entomology Circular 311), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 2001.